Rio Mamore Hantavirus Endemicity, Peruvian Amazon, 2020 - Marta Piche-Ovares; Maria Paquita García; Andres Moreira-Soto; Maribel Dana Figueroa-Romero; Nancy Susy Merino-Sarmiento; Adolfo Ismael Marcelo-Ñique; Edward Málaga-Trillo; Dora Esther Valencia Manosalva; Miladi Gatty-Nogueira; César Augusto Cabezas Sanchez; Jan Felix Drexler (Emerging Infectious Diseases)
To explore hantavirus infection patterns in Latin America, we conducted molecular and serologic hantavirus investigations among 3,400 febrile patients from Peru during 2020–2021. Reverse transcription PCR indicated that a patient from Loreto, in the Peruvian Amazon, was positive for Rio Mamore hantavirus (serum, 3.8 × 103 copies/mL). High genomic sequence identity of 87.0%–94.8% and phylogenetic common ancestry with a rodent-associated Rio Mamore hantavirus from Loreto in 1996 indicated endemicity. In 832 samples from Loreto, hantavirus incidence based on IgM ELISA of pooled Sin Nombre (SNV) and Andes virus (ANDV) nucleoproteins and immunofluorescence assay–based end-point titration using SNV/ANDV/Hantaan/Puumala/Saarema/Dobrava/Seoul hantaviruses was 0.5%. Across 3 ecologically distinct departments in Peru, SNV/ANDV IgG ELISA/IFA–based reactivity was 1.7%, suggesting circulation of antigenically distinct New World hantaviruses. Testing for arboviruses, nonendemic pathogens, and antigen-free ELISA corroborated nonspecific reactivity in 2 IgG and several IgM ELISA–positive serum samples. Hantavirus diagnostics and surveillance should be strengthened in Peru ad across Latin America.